Safety and efficacy of incobotulinumtoxinA as a potential treatment for poststroke spasticity - Santamato A (Dove Medical Press, 2016)
Andrea Santamato Physical Medicine and Rehabilitation Section, “OORR Hospital,” University of Foggia, Foggia, Italy Abstract: Spasticity is a common disabling symptom for several neurological conditions. Botulinum toxin type A injection represents the gold standard treatment for focal spasticity after stroke showing efficacy, reversibility, and low prevalence of complications. In recent years, incobotulinumtoxinA, a new Botulinum toxin type A free of complexing proteins, has been used for treating several movement disorders with safety and efficacy. IncobotulinumtoxinA is currently approved for treating spasticity of the upper limb in stroke survivors, even if several studies described the use also in lower limb muscles. In the present review article, we examine the safety and effectiveness of incobotulinumtoxinA for the treatment of spasticity after stroke. Keywords: Hypertone, botulinum toxin, incobotulinumtoxinA, onabotulinumtoxinA, abobotulinumtoxinA